IMPLEMENTASI TRIPLE HELIX DALAM MENDORONG PERTUMBUHAN DESA WISATA PERTANIAN ORGANIK DESA KANIGORO SEBAGAI UPAYA MENCIPTAKAN LAPANGAN PEKERJAAN (Studi Pada Desa Wisata Pertanian Organik Kanigoro Kec. Pagelaran Kab. Malang) - Sevrilia Budi Pratiwi; Abdul Kodir Djaelani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract This study Intends: 1) to find out and analyze the role of academics and industry in creating organic agricultural tourism in Kanigoro Village. 2) to find and analyze the factors that play a role in the development of organic agricultural tourism in Kanigoro Village. The speakers in this study consisted of Mr. Basiri as the head of the P4S Bengkel Mimpi, Mr. Ishaq as one of the P4S Bengkel Mimpi administrators, Mr. Mujib as the village apparature, Mr. Nazil as an industry player, Mas Robit as a student of Brawijaya University, Mr. Min as a resident of Kanigoro Village and Mr. Dwi as the field officer of the Malang Regency Agriculture and Food Crops Service.The results of the study explained that academics played an important role in mapping the problems and potentials of developing Kanigoro Village through various studies conducted from various disciplines so that it was found that Kanigoro Village has the potential to become an organic agricultural tourism village. The Kanigoro Village Government and the Malang Regency Agriculture and Food Crops Office played a role in promoting activities that were participated in both regional and national scales. The next actor is a business / industry actor who applies organic vegetable products in Kanigoro Village to the city. Furthermore, the factors that play an important role are the agricultural potential of Kanigoro Village, the desire to change and the use of digital media. Factors that inhibit financial shortages and loyalty of basic opinions are Mr. Basiri and the people of Kanigoro Village.Keywords: Triple Helix, Organic Farming TourismPendahuluan